Preparation technology of high-temperature-resistant epoxy energy storage film based on liquid crystal ordered structure

Through the preparation technology based on the ordered structure of liquid crystal, epoxy energy storage films with high dielectric constant and high energy storage density were prepared, which solved the problem of degradation in energy storage performance of existing dielectric materials in high temperature environments and realized the application of high-performance epoxy materials.

CN119684655AActive Publication Date: 2025-03-25XI'AN UNIVERSITY OF ARCHITECTURE AND TECHNOLOGY
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510056609.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-14
Publication Date
2025-03-25
Estimated Expiration
2045-01-14

AI Technical Summary

Technical Problem

The energy storage performance of existing dielectric materials has dropped sharply in high temperature environments, and the dielectric constant and dielectric strength are difficult to coordinately improve, which cannot meet the high energy storage density and heat resistance requirements for applications such as smart grids and electric vehicles.

Method used

Using the preparation technology based on the ordered structure of liquid crystal, epoxy energy storage film with high dielectric constant and high energy storage density is prepared by combining liquid crystal biphenyl epoxy monomer, bisphenol A type epoxy monomer and curing agent, magnetic stirring and oil bath heating and melting treatment, degassing and hot pressing curing, and an epoxy energy storage film with high dielectric constant and high energy storage density is prepared.

Benefits of technology

The high working temperature and high energy storage density of epoxy films have been achieved, which improves its heat resistance, thermal conductivity and mechanical properties, solves the problem of sharp decline in energy storage performance of commercial dielectric films, and provides new ideas for high-performance epoxy materials for the field of dielectric energy storage.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119684655A_ABST
    Figure CN119684655A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation technology of a high-temperature-resistant epoxy energy storage film based on a liquid crystal ordered structure, which comprises the following steps: S1, mixing a liquid crystal biphenyl type epoxy monomer, a bisphenol A type epoxy monomer and a curing agent in proportion, and simultaneously carrying out magnetic stirring and oil bath heating melting treatment to obtain a mixed melt; s2, carrying out degassing treatment on the mixed molten liquid obtained in the S1, and then pouring the mixed molten liquid into a mold; and carrying out heating curing treatment by adopting a hot-pressing method to obtain the epoxy film. According to the preparation technology of the high-temperature-resistant epoxy energy storage film based on the liquid crystal ordered structure, high-polarity fluorocarbon bonds are introduced into the liquid crystal molecule modified epoxy film, so that the energy storage density of the epoxy film is improved, a relatively high glass-transition temperature can be kept, the high-temperature energy storage characteristic of the epoxy film is improved, and the high-temperature-resistant epoxy energy storage film is prepared. And meanwhile, the cured epoxy film has a liquid crystal ordered structure, so that the thermal conductivity is synchronously improved, and a new idea is provided for developing a high-performance epoxy material in the field of dielectric energy storage.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of dielectric energy storage technology, and in particular to a preparation technology of a high temperature resistant epoxy energy storage film based on a liquid crystal ordered structure. Background Art

[0002] Power devices such as high-voltage insulated gate bipolar transistors (IGBTs) are widely used in ultra-high voltage (UHV) polymer dielectrics. They have the advantages of high dielectric constant, low dielectric loss, high power density, high charge and discharge efficiency, large operating voltage / current, high reliability and low cost. They are widely used as energy storage materials for capacitors such as smart grid high-power rapid regulation and electric vehicle AC / DC conversion. As decentralized renewable energy generation is incorporated into the power system, the load of the distributed power grid increases and the supply and demand control becomes complicated. Therefore, to achieve rapid regulation of high power in smart grids, capacitors with higher energy storage density and lower dielectric loss are required.

[0003] Biaxially oriented polypropylene (BOPP) has extremely low dielectric loss (tanδ≈4.0×10 -4 ), high dielectric strength and excellent tensile properties and are widely used as commercial energy storage dielectrics. However, due to its low dielectric constant (ε r =2.2), at a working electric field strength of 200kV / mm, the BOPP energy storage density (E w ) is only 0.5J / cm 3 In practical applications, it is often necessary to increase the amount of material used to meet the capacity requirements. At the same time, the volume of the capacitor will increase due to the increase in the amount of material used, making it increasingly difficult to meet the growing capacity requirements of power inverters in limited space.

[0004] In the prior art, the dielectric constant and dielectric strength of dielectric materials are contradictory. Improving the dielectric constant of dielectric materials will increase the dielectric loss of the material, resulting in an increase in leakage current, which in turn has a negative impact on the dielectric strength. How to synergistically improve the dielectric constant and dielectric strength of dielectric materials or improve the dielectric constant without affecting the dielectric strength has become the focus of research on polymer energy storage dielectric materials. In addition, in AC / DC conversion applications, affected by the highly integrated and miniaturized development process of power units and the difficulty of heat dissipation, the operating temperature of electronic devices continues to rise, and the heat resistance requirements of capacitors are getting higher and higher. For example, the operating environment temperature of the power inverter in electric vehicles has reached 110-120°C. At present, the operating temperature of commercial BOPP is relatively low. When the ambient temperature is higher than 85°C, its dielectric loss and charge and discharge efficiency (η) will be severely deteriorated, and additional space is required to install cooling devices, which further limits the application of BOPP in electric vehicle power inverters and smart grids. Therefore, it is urgent to develop energy storage dielectric materials with high operating temperature and high energy storage density. Summary of the invention

[0005] The purpose of the present invention is to provide a preparation technology of a high-temperature resistant epoxy energy storage film based on a liquid crystal ordered structure, improve the high-temperature energy storage characteristics of the epoxy film, solve the problem of a sharp decline in the energy storage performance of commercial dielectric films, and provide a new idea for the development of high-performance epoxy materials for the field of dielectric energy storage.

[0006] To achieve the above object, the present invention provides a preparation technology of a high temperature resistant epoxy energy storage film based on a liquid crystal ordered structure, comprising the following steps:

[0007] S1. Mix liquid crystal biphenyl epoxy monomer (TMBP), bisphenol A epoxy monomer (EP-828) and curing agent in proportion, and perform magnetic stirring and oil bath heating melting treatment at the same time to obtain a mixed molten liquid;

[0008] S2, degassing the mixed molten liquid obtained in S1, and then pouring it into a mold; heating and curing it by hot pressing to obtain an epoxy film.

[0009] Preferably, in S1, the curing agent includes 2,3,4-trifluoroaniline (TFAn) and 4,4-diaminodiphenylmethane (DDM).

[0010] Preferably, in S1, the liquid crystal biphenyl epoxy monomer may be 3,3,5,5-tetramethylbiphenyl bisphenol diglycidyl ether (TMBP). The liquid crystal ordered structure of TMBP helps to improve the breakdown field strength E b , thermal conductivity and heat resistance characteristics.

[0011] Preferably, in S1, the sum of the molar numbers of the bisphenol A type epoxy monomer and the liquid crystal biphenyl type epoxy monomer: the curing agent=3:2.

[0012] Preferably, in S1, the magnetic stirring and oil bath heating melting treatment are specifically:

[0013] A magnetic bar was added, and the mixture was heated and melted in an oil bath using a magnetic stirrer while being magnetically stirred.

[0014] Preferably, the oil bath heating temperature is 105° C., the stirring rate is 150-250 r / min, and the stirring time is 10 min.

[0015] Preferably, in S2, the degassing treatment is specifically:

[0016] The mixed molten liquid is placed in a vacuum drying oven and heated under reflux until no bubbles are generated.

[0017] Considering that bubbles may be generated in the process of mixing the molten liquid, resulting in uneven components in the obtained mixed molten liquid, and a large number of bubble defects will lead to reduced breakdown, the mixed molten liquid is first degassed before solidification to eliminate bubbles in the mixed molten liquid, thereby reducing the probability of insulation failure.

[0018] Preferably, the degassing treatment temperature is 105-110° C., and the degassing time is 3-5 min.

[0019] Preferably, in S2, the heat curing treatment by hot pressing is specifically:

[0020] First, the mold is preheated, and then a PET release film is placed under the mold. The degassed mixed molten liquid is poured into a copper foil mold with a thickness of 10μm. Then another PET release film is covered on top of the mold, placed in the middle of a mirror-smooth stainless steel plate, and put into a hot press for step-by-step heating and curing.

[0021] Considering that the mixed molten liquid is prone to low-temperature crystallization when exposed to low temperature, resulting in incomplete curing reaction, in order to avoid this situation, the present invention first preheats the mold to the curing temperature, then pours the degassed mixed solution into it, and then performs curing treatment. The pouring method is used, and the temperature of the mixed molten liquid during pouring is the temperature after degassing, 105°C.

[0022] Preferably, the temperature of the preheating treatment is 100-110° C., the temperature of the heating curing treatment is 105-200° C., and the curing time is 10 hours.

[0023] In the process of curing, the present invention takes into account that the curing process of the liquid crystal biphenyl epoxy monomer consists of early segment extension, branching and cross-linking reactions. The curing temperature has a great influence on the linear segment extension of the biphenyl liquid crystal unit, which is important for the π-π stacking interaction of the biphenyl liquid crystal unit. Therefore, in order to allow the liquid crystal biphenyl epoxy monomer to have sufficient time to achieve effective line segment extension and form liquid crystal domains, with a more complete degree of curing and a higher degree of crosslinking, the present invention preferably adopts a step-by-step temperature increase curing process for curing treatment, and the preferred curing process of the present invention is: first, in a hot press, curing at a curing temperature of 110°C for 4 hours, then curing at a curing temperature of 160°C for 4 hours, and finally curing at a curing temperature of 200°C for 2 hours, which is divided into three stages for step-by-step temperature increase. The treatment temperature of the first stage is lower than the curing temperature of the liquid crystal biphenyl epoxy monomer and the curing agent used. At this stage, the biphenyl liquid crystal unit can produce a π-π superposition effect, which helps these units to self-assemble and orient to form liquid crystal domains, and form a 20um film under a pressure of 200kPa, and continue to cure at 160°C for 4 hours and 200°C for 2 hours to ensure complete branching and crosslinking.

[0024] Therefore, the present invention adopts the above-mentioned preparation technology of high temperature resistant epoxy energy storage film based on liquid crystal ordered structure, and the beneficial effects are as follows:

[0025] The present invention uses liquid crystal biphenyl epoxy monomer (TMBP) and bisphenol A epoxy monomer (EP) as a matrix, intrinsically regulates the structure and curing temperature of curing agents (TFAn and DDM), and introduces high-polarity carbon-fluorine bonds into liquid crystal molecule-modified epoxy films to prepare a novel high-temperature resistant epoxy energy storage film based on a liquid crystal ordered structure, characterizes its electrical and thermal properties, and proves that the method can prepare energy storage dielectric materials with high operating temperature and high energy storage density.

[0026] The present invention introduces a liquid crystal biphenyl epoxy monomer as a rigid group, which can not only improve the heat resistance of the polymer dielectric, but also reduce its dielectric loss and improve the charge and discharge efficiency. Compared with the traditional filled epoxy resin, the biphenyl structure in its molecular structure has greater rigidity, so that the resistance to the internal rotation of the bond and the molecular chain is further enhanced. Therefore, the introduction of the liquid crystal biphenyl structure can effectively enhance the heat resistance of the epoxy film, and the liquid crystal molecule has excellent electrical insulation performance. Introducing liquid crystal molecules into the epoxy film can effectively improve the heat resistance, thermal conductivity and mechanical properties of the film.

[0027] The present invention introduces liquid crystal molecules into the epoxy film cross-linking network (TMBP / DDM) to effectively improve the rigidity of the molecular chain segments. However, the improvement of the rigidity of the molecular chain segment cross-linking structure will limit the polarization of the molecular chain segments, making the dielectric constant of the epoxy film relatively low, resulting in insufficient energy storage density. In view of the problem of insufficient dielectric constant, the introduction of highly polarized carbon-fluorine bonds into the liquid crystal molecule modified epoxy resin (TMBP / EP11) cross-linking system can effectively improve the dielectric constant and energy storage density of the epoxy film. The introduction of TFAn with an amine group at one end can also adjust the cross-linking degree of the epoxy film, thereby achieving control of film-forming ability and mechanical properties.

[0028] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 The infrared spectra of the epoxy films prepared in Examples 1 to 5 of the present invention;

[0030] Figure 2 The cross-sectional structure and planar structure SEM images of the epoxy films prepared in Examples 1, 3 and 5 of the present invention, wherein (a) is the cross-sectional morphology observed by SEM of Example 1, (b) is the cross-sectional morphology observed by SEM of Example 3, (c) is the cross-sectional morphology observed by SEM of Example 5, (d) is the surface morphology observed by SEM of Example 1, (e) is the surface morphology observed by SEM of Example 3, and (f) is the surface morphology observed by SEM of Example 5;

[0031] Figure 3 The DSC test results of the epoxy films prepared in Examples 1 to 5 of the present invention;

[0032] Figure 4 The tensile properties test results of the epoxy films prepared in Examples 1 to 5 of the present invention;

[0033] Figure 5 The axial thermal conductivity test results of the epoxy films prepared in Examples 1 to 5 of the present invention;

[0034] Figure 6 The planar thermal conductivity test results of the epoxy films prepared in Examples 1 to 5 of the present invention;

[0035] Figure 7 The dielectric properties test results of the epoxy films prepared in Examples 1 to 5 of the present invention;

[0036] Figure 8 The electric dipole moment results of the molecules obtained by quantum chemical calculations for Examples 1, 3 and 5 of the present invention, wherein (a) is Example 1, (b) is Example 3, and (c) is Example 5;

[0037] Fig. 9 The dielectric spectrum test results of the epoxy films prepared in Examples 1 to 5 of the present invention at different temperatures, wherein (a) is Example 1, (b) is Example 3, (c) is Example 5, and (d) is a comparison of the dielectric loss of the three films at 10 Hz and different temperatures;

[0038] Fig.10 Comparison of DC dielectric strength of epoxy films prepared in Examples 1 to 5 of the present invention;

[0039] Fig.11 The calculation results of the electrostatic potential distribution on the electron charge density isosurface based on density functional theory for Example 1, Example 3 and Example 5 of the present invention, wherein (a) is Example 1, (b) is Example 3, and (c) is Example 5;

[0040] Fig.12 Schematic diagram of the cross-linked structure of the molecular chains of Example 1, Example 3, and Example 5 of the present invention, wherein (d) is Example 1, (e) is Example 3, and (f) is Example 5;

[0041] Fig.13 The free volume ratio calculation results of three cross-linking systems based on the Forcite module in Examples 1, 3 and 5 of the present invention, wherein (g) is Example 1, (h) is Example 3, and (i) is Example 5;

[0042] Fig.14 The results of DC breakdown tests of epoxy films prepared in Examples 1, 3 and 5 of the present invention at different temperatures, wherein (a) is Example 1, (b) is Example 3, and (c) is Example 5;

[0043] Fig.15 The partial discharge test results of the epoxy films prepared in Examples 1, 3 and 5 of the present invention, wherein (a) is Example 1, (b) is Example 3, (c) is Example 5, and (d) is the average partial discharge amount;

[0044] Fig.16 The results of thermal stimulation current analysis of the epoxy films prepared in Examples 1 and 3 of the present invention, where (a) is the thermal stimulation current, (b) is the peak fitting of the TMBP / EP11 system, and (c) is the peak fitting of the 3F@TMBP / EP11 system;

[0045] Fig.17 The high temperature conductivity test results of the epoxy films prepared in Examples 1 and 3 of the present invention;

[0046] Fig.18The hysteresis loop results of epoxy films prepared in Examples 1 to 5 of the present invention at different electric field strengths and different test temperatures, wherein (a) is Example 1, (b) is Example 2, (c) is Example 3, (d) is Example 4, (e) is Example 5, (f) is the same electric field strength condition, (g) is Example 1 under different test temperature conditions, (h) is Example 3 under different test temperature conditions, and (i) is Example 5 under different test temperature conditions;

[0047] Fig.19 The energy storage performance comparison results of the epoxy films prepared in Examples 1 to 5 of the present invention, wherein (a) is room temperature conditions, (b) is different temperature conditions, (c) is a comparison of the energy storage density of this study and other research or commercial films at room temperature and with a charge and discharge efficiency greater than 90%, and (d) is a comparison of the charge and discharge efficiency of this study and other research or commercial films at 140°C and 200kV / mm;

[0048] Fig. 20 The epoxy film prepared in Example 3 of the present invention was tested for high temperature energy storage cycle performance at 200 kV / mm and at different temperatures;

[0049] Fig.21 A schematic diagram of the self-repairing process of the metallized film of the present invention;

[0050] Fig. 22 The morphology comparison before and after breakdown and the energy storage performance comparison test results of the epoxy film prepared in Example 3 of the present invention are shown, wherein (a) is a scanning electron microscope image before breakdown, (b) is an energy dispersion spectrometer analysis before breakdown, (c) is a polarizing microscope image after breakdown, (d) is a scanning electron microscope image after breakdown, (e) is an energy dispersion spectrometer analysis after breakdown, and (f) is a comparison of energy storage performance before and after breakdown. DETAILED DESCRIPTION

[0051] The technical solution of the present invention is further described below through the accompanying drawings and embodiments.

[0052] Unless otherwise defined, technical or scientific terms used in the present invention shall have the common meanings understood by one having ordinary skills in the field to which the present invention belongs.

[0053] Example 1

[0054] This embodiment provides a high temperature resistant epoxy energy storage film based on a liquid crystal ordered structure and its preparation technology is as follows:

[0055] 0.5g of TMBP, 0.5g of EP, and 0.272g of DDM were mixed and put into a magnetic particle. The mixture was placed in a 105℃ oil bath and heated to melt using a magnetic stirrer and magnetically stirred for 10 minutes. After stirring, the magnetic particle was sucked out using a magnet. The obtained mixed molten liquid was then placed in a vacuum drying oven at 90℃ for degassing until no bubbles were generated. A PET release film was placed under the mold, and the degassed mixed molten liquid was poured into a copper foil mold with a thickness of 20μm. Finally, another PET release film was covered on the mold and placed in the middle of a mirror-grade smooth stainless steel plate. It was cured in a hot press at a curing temperature of 110℃ for 4h, then at a curing temperature of 160℃ for 4h, and finally at a curing temperature of 200℃ for 2h. An epoxy film with both heat resistance and energy storage performance was obtained, which was named TMBP / EP11.

[0056] Example 2

[0057] This embodiment provides a high temperature resistant epoxy energy storage film based on a liquid crystal ordered structure and its preparation technology is as follows:

[0058] 0.5g of TMBP, 0.5g of EP, 0.265g of DDM and 0.015g of TFAn were mixed and put into a magnetic bar. The mixture was placed in a 105℃ oil bath and heated to melt using a magnetic stirrer and magnetically stirred for 10min. After stirring, the magnetic bar was sucked out using a magnet. The obtained mixed melt was then placed in a vacuum drying oven at 90℃ for degassing until no bubbles were generated. A PET release film was placed under the mold, and the degassed mixed melt was poured into a copper foil mold with a thickness of 20μm. Finally, another PET release film was covered on the mold and placed in the middle of a mirror-grade smooth stainless steel plate. It was cured in a hot press at a curing temperature of 110℃ for 4h, then at a curing temperature of 160℃ for 4h, and finally at a curing temperature of 200℃ for 2h. An epoxy film with both heat resistance and energy storage performance was obtained, which was named 1F@TMBP / EP11.

[0059] Example 3

[0060] This embodiment provides a high temperature resistant epoxy energy storage film based on a liquid crystal ordered structure and its preparation technology is as follows:

[0061] 0.5g of TMBP, 0.5g of EP, 0.247g of DDM and 0.04g of TFAn were mixed and put into a magnetic particle. The mixture was placed in a 105℃ oil bath and heated to melt using a magnetic stirrer and magnetically stirred for 10min. After stirring, the magnetic particle was sucked out using a magnet. The obtained mixed molten liquid was then placed in a vacuum drying oven at 90℃ for degassing until no bubbles were generated. A PET release film was placed under the mold, and the degassed mixed molten liquid was poured into a copper foil mold with a thickness of 20μm. Finally, another PET release film was covered on the mold and placed in the middle of a mirror-grade smooth stainless steel plate. It was cured in a hot press at a curing temperature of 110℃ for 4h, then at a curing temperature of 160℃ for 4h, and finally at a curing temperature of 200℃ for 2h. An epoxy film with both heat resistance and energy storage performance was obtained, which was named 3F@TMBP / EP11.

[0062] Example 4

[0063] This embodiment provides a high temperature resistant epoxy energy storage film based on a liquid crystal ordered structure and its preparation technology is as follows:

[0064] 0.5g of TMBP, 0.5g of EP, 0.22g of DDM and 0.08g of TFAn were mixed and put into a magnetic particle. The mixture was placed in a 105℃ oil bath and heated to melt using a magnetic stirrer and magnetically stirred for 10min. After stirring, the magnetic particle was sucked out using a magnet. The obtained mixed melt was then placed in a vacuum drying oven at 90℃ for degassing until no bubbles were generated. A PET release film was placed under the mold, and the degassed mixed melt was poured into a copper foil mold with a thickness of 20μm. Finally, another PET release film was covered on the mold and placed in the middle of a mirror-grade smooth stainless steel plate. It was cured in a hot press at a curing temperature of 110℃ for 4h, then at a curing temperature of 160℃ for 4h, and finally at a curing temperature of 200℃ for 2h. An epoxy film with both heat resistance and energy storage performance was obtained, which was named 6F@TMBP / EP11.

[0065] Example 5

[0066] This embodiment provides a high temperature resistant epoxy energy storage film based on a liquid crystal ordered structure and its preparation technology is as follows:

[0067] 0.5g of TMBP, 0.5g of EP, 0.183g of DDM and 0.13g of TFAn were mixed and put into a magnetic particle. The mixture was placed in a 105℃ oil bath and heated to melt using a magnetic stirrer and magnetically stirred for 10min. After stirring, the magnetic particle was sucked out using a magnet. The obtained mixed melt was then placed in a vacuum drying oven at 90℃ for degassing until no bubbles were generated. A PET release film was placed under the mold, and the degassed mixed melt was poured into a copper foil mold with a thickness of 20μm. Finally, another PET release film was covered on the mold and placed in the middle of a mirror-grade smooth stainless steel plate. It was cured in a hot press at a curing temperature of 110℃ for 4h, then at a curing temperature of 160℃ for 4h, and finally at a curing temperature of 200℃ for 2h. A new type of energy storage epoxy film with high heat resistance and high thermal conductivity and a liquid crystal ordered structure was obtained, which was named 10F@TMBP / EP11.

[0068] Experimental Testing

[0069] (I) Molecular structure characterization

[0070] like Figure 1 As shown, the infrared spectra of epoxy films and standard TMBP prepared in Examples 1 to 5 with different cross-linking curing systems after normalization. -1 The hydroxyl stretching is at 2800-3100cm -1 Alkyl stretching, 1450-1600cm -1 Aromatic stretching, 1000-1200cm -1 The carbon-oxygen bond stretches at 3200-3400cm -1 The characteristic peak of secondary amine (brown shadow) is at 913cm -1 The characteristic peak of epoxy group (blue shadow) is at 1220-1245cm. No obvious characteristic peaks were found in the above two places, which proved that the two epoxy resins and curing agents had reacted completely. -1 It is the characteristic peak of carbon-fluorine bond. When carbon-fluorine bond is introduced into the cross-linking system, the gradient change of the peak value of the five systems in this range can be clearly observed, indicating that the four carbon-fluorine bond modified systems have successfully grafted carbon-fluorine bonds.

[0071] (II) Morphological characterization

[0072] The epoxy films prepared in Example 1, Example 3 and Example 5 were tested for morphology using a field emission electron microscope (SEM, Zeiss Gemini SEM500). The test results are shown in FIG. Figure 2As shown. It can be observed that with the increase in the amount of carbon-fluorine bonds introduced, the film cross section and cross section become smoother and smoother. There are many serrated lines on the cross section of the TMBP / EP11 cross-linking system, the serrated lines on the cross section of the 3F@TMBP / EP11 cross-linking system are significantly reduced, and almost no obvious lines can be observed on the cross section of the 10F@TMBP / EP11 cross-linking system. This is because when TFAn is used as a curing agent, it can only link two epoxy molecular chains, while DDM can link four epoxy molecular chains. Therefore, the cross-linking degree of the cross-linking structure will decrease with the increase in the amount of carbon-fluorine bonds introduced. The reduction in the cross-linking degree can effectively reduce the restrictions on the activity of the molecular chain segments, thereby enhancing the flexibility of the cross-linking system, which is conducive to its application in the roll-to-roll process of metal film capacitors.

[0073] (III) DSC test

[0074] like Figure 3 As shown in the figure, it can be seen from the Tg curve of the epoxy film that with the increase of the introduction amount of TFAn, the glass transition temperature of the epoxy film has decreased significantly. The results show that the glass transition process of the polymer material corresponds to the static-dynamic transition process of its cross-linked structure segment. The electron clouds of the polymer overlap to form asymmetric large π bonds, which makes the internal rotation of the molecular chain more difficult. Polymers containing conjugated double bonds such as benzene rings have greater rigidity and excellent heat resistance. Although TFAn contains an aromatic ring structure, the introduction of TFAn will cause the cross-linking degree of the molecular chain segment cross-linking system to decrease. The decrease in the cross-linking degree will reduce the constraint on the movement of the chain segment, thus causing the glass transition temperature to decrease. However, compared with ordinary epoxy resin, the Tg after the introduction of TFAn is still higher. The Tg value of 10F@TMBP / EP11 with the worst heat resistance can still reach 135℃, which can basically meet the application of power inverters in general high-temperature working environments. The mechanical properties of epoxy films are of great significance to their practical applications.

[0075] (IV) Tensile performance test

[0076] like Figure 4 As shown, five epoxy films were tensile tested. Among them, the tensile fracture strength of the TMBP / EP11 system without the introduction of TFAn was 64.22Mpa. After the introduction of 1wt%, 3wt%, 6wt% and 10wt% TFAn, the tensile fracture strength decreased by 8.3%, 8.5%, 27% and 38%, respectively. It can be found that after the introduction of TFAn, the overall tensile fracture strength decreased to varying degrees. When the introduction amount is small (<3wt%), the decrease is not obvious. When the introduction amount exceeds 6wt%, the tensile fracture strength drops sharply. The elongation at break will be significantly improved when the introduction amount is small, which can effectively improve the flexibility of the polymer matrix. When the introduction amount exceeds a certain level, the degree of crosslinking decreases significantly. At this time, the elongation at break is affected by the fracture strength and also drops sharply.

[0077] (V) Thermal conductivity test

[0078] Figure 5 and Figure 6 They are the test results of axial thermal conductivity and planar thermal conductivity of different cross-linking systems. Both tests show the same trend, that is, the decrease in the degree of cross-linking of the cross-linking system has a strong scattering effect on phonon transmission, resulting in a decrease in the mean free path of phonon transmission, which is not conducive to the formation of thermal conduction pathways and the diffusion of heat. Compared with TMBP / EP11, the axial thermal conductivity of the epoxy films introducing 1wt%, 3wt%, 6wt% and 10wt% TFAn decreased by 4.1% (0.322W / mK), 8.9% (0.306W / mK), 19.3% (0.271W / mK) and 28% (0.242W / mK), respectively, and the axial thermal conductivity of TMBP / EP11 was 0.336W / mK; the planar thermal conductivity decreased by 10% (0.99W / mK), 20% (0.88W / mK), 34% (0.725W / mK) and 32% (0.753W / mK), respectively, and the planar thermal conductivity of TMBP / EP11 was 1.1W / mK. It can be found that similar to the changing trend of the tensile test results, when a small amount of TFAn is introduced, the thermal conductivity of the epoxy film decreases relatively little. When the introduced amount is greater than 6wt%, the thermal conductivity also decreases significantly due to the large decrease in cross-linking degree.

[0079] (VI) Dielectric properties characterization

[0080] 1) Study on the mechanism of the effect of the amount of carbon-fluorine bond introduction on the dielectric properties of epoxy films

[0081] Figure 7The dielectric properties of different epoxy films at room temperature (25°C). Before the introduction of TFAn, the dielectric constant of TMBP / EP11 was relatively low, which was 4.36 at 10Hz. After the introduction of TFAn, the dielectric constants at 10Hz were 4.76 (1F@TMBP / EP11), 5.09 (3F@TMBP / EP11), 5.25 (6F@TMBP / EP11) and 5.69 (10F@TMBP / EP11), respectively. The increase in the dielectric constant due to the strong polar carbon-fluorine bond is the same as the change trend of the TFAn content in the system. There are two main reasons. First, after the introduction of high-polarity carbon-fluorine bonds, the polarization properties of the molecular chain segments are greatly improved. Second, the introduction of carbon-fluorine bonds is reflected by adding TFAn to the curing system. Unlike the curing agent DDM, which can link four epoxy molecular chains, the TFAn molecule contains only one secondary amine group and can only link two epoxy molecular chains. Therefore, the cross-linking density of the cross-linking system will decrease, and the movement of the molecular chain segments will be less restricted, which is conducive to the directional movement of the molecular chain segments under the action of the external electric field. To verify this theory, molecular simulation calculations were performed. The Dmol3 module in Material Studio was used to optimize the calculation of the minimum repeating unit of the cross-linking structure. The electric dipole moment of the molecule was obtained by quantum chemical calculation, as shown in Table 1.

[0082] Table 1 Direction and magnitude of dipole moment vector

[0083] Curing system x y z Dipole magnitude / au TMBP / EP11 0.360839 0.336043 1.839466 4.8406 3F@TMBP / EP11 2.044803 1.418162 1.351327 7.1975 10F@TMBP / EP11 -2.307237 1.445727 2.528565 9.4447

[0084] like Figure 8 As shown in Table 1, 3F@TMBP / EP11 and 10F@TMBP / EP11 exhibit higher dipole moments and stronger molecular polarity compared with the TMBP / EP11 system. More precisely, the mean square dipole moment of the 3F@TMBP / EP11 system is calculated to be 7.1945 Debye, which is nearly 1.48 times that of the TMBP / EP11 system (4.8406 Debye), and the mean square dipole moment of the 10F@TMBP / EP11 system is 9.4447 Debye, which is nearly 1.95 times that of the TMBP / EP11 system (as shown in Table 1). The high dipole moments of the 3F@TMBP / EP11 and 10F@TMBP / EP11 systems may be contributed by two parts. First, due to the close bonding of chemical bonds, the reduced crosslinking degree of the crosslinked network contributes to the dipole moment. Second, the CF bond with high polarity plays an important role in enhancing the dipole moment.

[0085] 2) Study on the mechanism of temperature effect on dielectric properties of epoxy films

[0086] like Fig. 9As shown, combined with the DSC test results, TMBP / EP11 has the best high temperature stability among the five systems, and its dielectric loss is still stable at 160°C. The system of Example 5 with the worst high temperature resistance can also remain relatively stable at 140°C. The above results show that, under the premise of having little effect on high temperature resistance, the introduction of high polarity carbon-fluorine bonds can effectively improve the dielectric constant of epoxy films without affecting the dielectric loss.

[0087] (VII) Dielectric strength characterization

[0088] 1) Study on the mechanism of the effect of the amount of carbon-fluorine bond introduction on the dielectric strength of epoxy films

[0089] Fig.10 The dielectric strength of epoxy films modified by liquid crystal molecules with different TFAn contents, the film thickness is 10 (± 1) μm. The test results were processed by Weibull distribution function, and the dielectric strength of epoxy films modified by carbon-fluorine bonds and liquid crystal molecules was obtained. The dielectric strength of the epoxy film before the introduction of TFAn was 569.8 kV / mm, and the dielectric strength of the epoxy film after the introduction of TFAn was 500.3 kV / mm (1wt%), 490 kV / mm (3wt%), 451.9 kV / mm (6wt%) and 442.9 kV / mm (10wt%) respectively. It can be found that with the increase of the amount of TFAn introduced, the dielectric strength of the cross-linked system at room temperature gradually decreases. There are two main reasons. First, with the introduction of TFAn, the content of the high-rigidity curing agent DDM in the system gradually decreases, the high-rigidity phenyl structure is relatively reduced, the restriction on the movement of free electrons is reduced, and the ability of the cross-linked structure to withstand the impact of free electrons also decreases. Second, the degree of crosslinking in the crosslinking system will decrease with the increase of TFAn content, that is, the energy barrier of molecular chain segment rotation will decrease, making it easier to turn, displace, and so on. The mean free path of free electrons will increase, and free electrons will be able to obtain greater kinetic energy to impact the crosslinking structure. To verify this theory, the electrostatic potential distribution on the electron charge density isosurface was calculated based on density functional theory. Fig.11 As shown, red and blue represent positive and negative potentials, respectively. It can be observed that the electrostatic potential of TMBP / EP11 is higher than that of 3F@TMBP / EP11 and 10F@TMBP / EP11. These results indicate that TMBP / EP11 has a stronger repulsive or attractive force on free electrons, which can effectively activate free electrons and reduce the kinetic energy and impact ionization of free electrons. Since there are relatively more DDM and phenyl structures in the TMBP / EP11 curing system, stronger electrostatic forces can be generated to repel or attract carriers. Stronger electrostatic forces and restrictions on the migration of current carriers will lead to more obvious trap effects, which can reduce the free path and energy of free electrons in the electric field. The calculation results show that due to stronger electrostatic forces and more obvious trap effects, TMBP / EP11 should have a higher Eb In addition to electrostatic potential, the mobility of molecular chains is another important factor that determines the dielectric breakdown strength of the cross-linked system.

[0090] The free volume ratios of the three cross-linked systems were calculated based on the Forcite module. First, the cross-linked structure of the molecular chain was optimized and annealed to obtain a more stable or lower energy structure, such as Fig.12 Then, we performed molecular dynamics simulation on the treated cross-linked structure and obtained its free volume, as shown in Fig.13 The free volume is shown in the blue part. The free volume refers to the atomic-sized defects and holes generated by the random stacking of atoms. According to the dielectric breakdown theory, the free volume can provide space for the migration of free electrons. The calculation results show that the free volume of TMBP / EP11 is larger than that of 3F@TMBP / EP11 and 10F@TMBP / EP11. The calculation results of the free volume ratio are shown in Table 2.

[0091] Table 2 Free volume ratio of different cross-linking systems

[0092]

[0093] From Table 2 combined with the electrostatic potential distribution, it can be seen that with the introduction of carbon-fluorine bonds, the dielectric strength of the epoxy film will decrease, which is consistent with the test results.

[0094] 2) Study on the mechanism of temperature effect on dielectric strength of epoxy film

[0095] Three different cross-linked structures (TMBP / EP11, 3F@TMBP / EP11, 10F@TMBP / EP11) were subjected to DC breakdown tests at different temperatures. The test results are shown in Figure 2. Fig.14 As shown. When the temperature gradually rises, the activity of the molecular chain segments is further enhanced. At this time, the mean free path of the free electrons is further increased, and the kinetic energy obtained by the free electrons increases. Therefore, the dielectric strength of each cross-linked system decreases with the increase of temperature. When the temperature rises to the glass transition temperature, the molecular chain segments begin to change from the glass state to the highly elastic state. At this time, the activity of the molecular chain segments reaches its peak. When the temperature continues to rise, the glass state-highly elastic state transition is completely completed. At this time, the dielectric strength of the cross-linked system will drop sharply.

[0096] To verify the repulsion and attraction of free electrons by a specific structure, partial discharge tests were performed, e.g. Fig.15 It was found that the amount of local discharge increased significantly after the introduction of TFAn, which was caused by the lack of specific structures in some molecular segments to restrict the movement of free electrons. This further verified that the high-rigidity curing agent can effectively inhibit the movement of free electrons and play a positive role in improving the dielectric strength of the system.

[0097] The trap distribution of epoxy film was obtained by thermally stimulated current analysis, such as Fig.16 The trap energy levels and trap charges of the two cross-linked systems were calculated using the half-peak width method, as shown in Table 3.

[0098] Table 3 Trap energy levels and trap charges of different epoxy films

[0099]

[0100] After the introduction of carbon-fluorine bonds, the trap energy level and trap charge of the cross-linked system are significantly reduced. This is because the cross-linking density of the cross-linked structure is reduced, resulting in a reduction in the deep traps of the polymer. At this time, the restriction effect of the cross-linked structure on free electrons is reduced, and the free electrons can obtain greater kinetic energy to impact the cross-linked structure, so the dielectric strength of the epoxy film is reduced.

[0101] In order to further verify the effect of carbon-fluorine bond introduction and temperature on the pressure resistance of the material, the conductivity of carbon-fluorine bond and liquid crystal molecule modified epoxy film at different temperatures was tested. The test results are as follows: Fig.17 As shown. The conductivity test results of TMBP / EP11 and 3F@TMBP / EP11 at different temperatures show the same results as the breakdown performance and thermal stimulation current tests. That is, with the introduction of carbon-fluorine bonds, the rigid structure of the molecular chain segments is relatively reduced, and the cross-linking density of the cross-linking structure is reduced, resulting in a reduction in the deep traps of the polymer. At this time, the restriction of the cross-linking structure on free electrons is reduced, so the conductivity increases. Comparing the conductivity test results of the same system at different temperatures, since the increase in temperature will lead to an increase in the carrier density, the conductivity will also tend to increase.

[0102] (VIII) Study on the energy storage properties of epoxy films modified by highly polarized carbon-fluorine bonds and liquid crystal molecules

[0103] 1) Study on polarization properties of epoxy films modified by carbon-fluorine bonds and liquid crystal molecules

[0104] Fig.18 The hysteresis loops of epoxy films at different electric field strengths and different test temperatures. The polarization strength of the film increases with the increase of the electric field strength. Combined with the dielectric spectrum test results, due to the extremely low dielectric loss of epoxy films, all films show very small hysteresis loss and very narrow hysteresis loops at room temperature, which provides an important guarantee for improving the charge and discharge efficiency.

[0105] In general, under the same electric field conditions, the electric displacement of the TMBP / EP11 system is the lowest. After the introduction of carbon-fluorine bonds, the electric displacement begins to gradually increase. This is due to the increase in the dielectric constant of the epoxy film after the introduction of carbon-fluorine bonds. High-polarity carbon-fluorine bonds can effectively promote the polarization enhancement of the cross-linked system. In order to study the effect of temperature change on the polarization properties of the cross-linked system, an electric field strength of 200kV / mm was selected, and hysteresis loop tests were carried out under different temperature conditions. When the ambient temperature is less than 120°C, the three films tested can maintain the performance at room temperature. When the temperature rises to 140°C, the hysteresis loops of the TMBP / EP11 system and 3F@TMBP / EP11 can still maintain a very narrow charge and discharge curve spacing, which is mainly due to their higher glass transition temperature. When the ambient temperature is within the glass transition temperature, its dielectric loss can remain stable. The glass transition temperature of the epoxy film of the 10F@TMBP / EP11 system is only 135°C. At this time, the ambient temperature is higher than its glass transition temperature, so its dielectric loss increases, causing the spacing between the hysteresis loop charge and discharge curves to begin to increase. When the ambient temperature further increases to 160°C, the spacing between the hysteresis loop charge and discharge curves of the 10F@TMBP / EP11 system further increases. Different from the 10F@TMBP / EP11 system, under the influence of the high glass transition temperature, TMBP / EP11 can still maintain low dielectric loss and narrow hysteresis loop at 160°C.

[0106] 2) Based on the hysteresis loop test results, the energy storage density and charge-discharge efficiency of each cross-linked system at different electric field strengths and temperatures were obtained by calculating the area integral. Fig.19 (a) shows the energy storage performance comparison of epoxy films modified by high polarized carbon-fluorine bonds and liquid crystal molecules at room temperature. As the amount of carbon-fluorine bonds introduced increases, the energy storage density of epoxy films under the same electric field shows an upward trend. For example, at room temperature and 400 kV / mm, the energy storage densities of the five epoxy films are 3.28 J / cm 3 (TMBP / EP11), 3.49J / cm 3 (1F@TMBP / EP11), 4.49J / cm 3 (3F@TMBP / EP11), 4.75J / cm 3 (6F@TMBP / EP11), 5.07J / cm 3(10F@TMBP / EP11). Due to its highest dielectric constant, 10F@TMBP / EP11 has the highest energy storage density under the same electric field strength. The five systems can still maintain a high charge and discharge efficiency of more than 90% at room temperature until electrical breakdown occurs. The lowest is the 1F@TMBP / EP11 system, which has a charge and discharge efficiency of 90.9% at room temperature and 540kV / mm. The low energy loss is conducive to the application of this study in high-frequency charge and discharge equipment.

[0107] like Fig.19 (b) shows the energy storage performance comparison of high polarized carbon-fluorine bonds and liquid crystal molecules modified epoxy films at different temperatures. Consistent with the high temperature dielectric spectrum test results, due to the sharp increase in dielectric loss, the charge and discharge efficiency of the 10F@TMBP / EP11 system dropped sharply after the test temperature exceeded 140°C. At 140°C and 200kV / mm, it can still maintain 0.95J / cm 3 and 88.3% of the energy storage performance. When the temperature rises to 160°C, its energy storage density drops to 0.62 J / cm 3 , the charge-discharge efficiency dropped to 47.2%. The 3F@TMBP / EP11 system exhibits stable and excellent energy storage performance at both room temperature and high temperature. At room temperature and 500kV / mm, the energy storage density and charge-discharge efficiency can reach 7.1J / cm 3 and 91.5%. At 140℃ and 200kV / mm, the energy storage density and charge-discharge efficiency can reach 1.01J / cm 3 and 94.3%. Under the conditions of 160℃ and 200kV / mm, the energy storage density and charge and discharge efficiency can reach 0.83J / cm℃ and 81.5% respectively.

[0108] like Fig.19As shown in (c), the energy storage density of 3F@TMBP / EP11 film is compared with other research or commercial films with a charge and discharge efficiency greater than 90% at room temperature. The energy storage density and charge and discharge efficiency of 3F@TMBP / EP11 film at room temperature and 500kV / mm are 7.1J / cm3 and 91.5%, respectively. Although linear dielectric materials such as polypropylene, polyimide, and polyetherimide have extremely high charge and discharge efficiencies, their low dielectric constants (<3.5) make it difficult to improve their energy storage density. Epoxy resin is a typical thermosetting polymer with linear polarization characteristics, and its tight cross-linked network gives it extremely high charge and discharge efficiency. The polar CN bonds in epoxy resin cured products make its dielectric constant higher (>4), and the introduction of high-polarity carbon-fluorine bonds further increases its dielectric constant to 5.1 at 10Hz. These factors ensure that the epoxy film has a high energy storage density under the premise of a charge and discharge efficiency greater than 90%. As Fig.19 (d) shows the comparison of the charge and discharge efficiency of the 3F@TMBP / EP11 film in this study with other research or commercial films at 140°C and 200kV / mm. The energy storage density and charge and discharge efficiency of the 3F@TMBP / EP11 film under these conditions are 1.02J / cm3 and 94.3%, respectively. For example, materials such as polycarbonate and polyetherimide are typical high-temperature resistant dielectric materials. The high rigidity groups in the molecular structure of the materials provide a guarantee for their high charge and discharge efficiency at high temperatures. Compared with common high-temperature resistant dielectric materials, the heat resistance of ordinary epoxy is far from enough. The present invention introduces liquid crystal molecules to construct a high-rigidity cross-linked structure through the curing reaction of epoxy and amine groups, thereby achieving the purpose of improving its heat resistance.

[0109] Based on the above results, the cycling performance of the 3F@TMBP / EP11 film in a high temperature environment was tested to evaluate the stability of the film in long-term use at high temperatures. Fig. 20 As shown in the figure, the high temperature energy storage cycle performance of 3F@TMBP / EP11 film was tested at 200kV / mm and different temperatures. After 10,000 cycles at 80°C and 140°C, the energy storage density and charge and discharge efficiency remained almost unchanged, indicating that the epoxy film has excellent reliability when used under 140°C and 200kV / mm conditions. The commercial BOPP film broke down at 120°C, 200kV / mm, and 10,000 cycles, and the energy storage density decreased by 16%. Compared with BOPP, the long-term stability of 3F@TMBP / EP11 film at high temperature is much superior.

[0110] 2) When film capacitors are used in engineering applications, long-term operating reliability and stability should be fully considered. In actual film capacitor applications, a large area of ​​dielectric polymer film is metallized, and metal is sprayed on both sides of the film as electrodes. In this structure, when the film breaks down locally during operation, the metallization layer can act as a fuse. Fig.21 As shown in the figure, the self-healing process of metallized film. Due to defects in the polymer, the local electric field may increase sharply, causing breakdown at the weak point. During the breakdown process, the ultra-high temperature (>8000K) breakdown arc quickly destroys the electrode material, while causing the polymer to decompose, releasing gases such as CO, H2, CH4, C2H2 and various chemical residues such as graphite solid phase. It is worth noting that the process of electrical breakdown of the material may also lead to the vaporization of the metal electrode on the surface of the film. In particular, when the newly exposed surface area under the metal electrode is large enough to isolate the carbonization perforation and the arc is extinguished in time, the film will achieve "self-repair" in terms of insulation function, and the subsequent film can continue to work normally in capacitor applications. On the contrary, the film will fail completely after a breakdown. During the self-healing process, dielectric defects can be eliminated in <10μs without any external operation, which helps to improve the reliability of the capacitor.

[0111] At present, the theoretical relationship between the chemical composition of polymer dielectrics and their self-healing ability has not been clearly verified. However, some research experience shows that there is a certain relationship between the chemical composition of polymer dielectrics and their self-healing ability. For polymer dielectrics with the general formula, the larger the ratio of and , the weaker the self-healing ability. When the above ratio is small, less graphite is deposited during its self-healing process, which prevents the formation of conductive graphite bridges and ultimately ensures its good self-healing performance. This ratio of PP and PET is 0.5 and 0.75, respectively, and both have good self-healing behavior. In the present invention, the ratio of 3F@TMBP / EP11 film and is about 0.68, and the self-healing ability is between PP and PET, which is much lower than PEI (1.3), PI (1.6) and PEEK (1.33). Fig. 22 As shown, the morphology and energy storage performance of the film before and after the initial breakdown are compared.

[0112] like Fig. 22As shown in (a)-(e) in the figure, the morphology of the film before breakdown and its element distribution were first observed by scanning electron microscopy and energy dispersive spectrometer. After the sample was broken down, polarizing microscope and scanning electron microscope observed holes with a diameter of 220μm. This is because there may be defects at the location of the holes. When an external electric field is applied to both sides of the electrode, local electric field distortion is formed at the defects, which eventually leads to breakdown. The polarizing microscope image clearly shows that the silver electrode around the breakdown hole disappears. The arc generated during breakdown usually generates strong Joule heat that not only damages the material, but also causes the evaporation of the surrounding silver electrodes. The above view can be further confirmed by the analysis results of the energy dispersive spectrometer after breakdown. Fig. 22 As shown in (f), during the first charge and discharge process, when 3F@TMBP / EP11 broke down at 500kV / mm, the 3F@TMBP / EP11 film was tested again and was still able to complete the charge and discharge process normally under an electric field of 450kV / mm. Before the breakdown, the energy storage density and charge and discharge efficiency of 3F@TMBP / EP11 at room temperature and 450kV / mm electric field were 5.583J / cm3 and 93.5%, respectively. After the breakdown, the energy storage density and charge and discharge efficiency of 3F@TMBP / EP11 under the same conditions were 5.359J / cm3 and 89.5%, respectively. Although the energy storage density and charge and discharge efficiency have decreased slightly, it still shows that the 3F@TMBP / EP11 film has successfully self-repaired.

[0113] In summary, introducing highly polarizable carbon-fluorine bonds into liquid crystal molecule-modified epoxy films can effectively improve the polarization properties of the films, thereby improving the energy storage density of the epoxy films, while still maintaining a relatively high glass transition temperature, thereby improving the high-temperature energy storage properties of the epoxy films.

[0114] Therefore, the present invention adopts the above-mentioned preparation technology of high-temperature resistant epoxy energy storage film based on liquid crystal ordered structure, and introduces high-polarity carbon-fluorine bonds into the liquid crystal molecule modified epoxy film to effectively improve the polarization performance of the film, thereby improving the energy storage density of the epoxy film, and still being able to maintain a relatively high glass transition temperature, thereby improving the high-temperature energy storage characteristics of the epoxy film, solving the problem of a sharp decline in the energy storage performance of commercial dielectric films, and providing a new idea for the development of high-performance epoxy materials for the field of dielectric energy storage.

[0115] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.

Claims

1. A preparation technology of high temperature resistant epoxy energy storage film based on liquid crystal ordered structure, characterized in that: The following steps are involved: S1, mixing a liquid crystal biphenyl epoxy monomer, a bisphenol A epoxy monomer and a curing agent in proportion, and simultaneously performing magnetic stirring and oil bath heating melting treatment to obtain a mixed molten liquid; S2, degassing the mixed molten liquid obtained in S1, and then pouring it into a mold; heating and curing it by hot pressing to obtain an epoxy film.

2. The preparation technology of a high temperature resistant epoxy energy storage film based on liquid crystal ordered structure according to claim 1, characterized in that: In S1, the curing agent includes 2,3,4-trifluoroaniline and 4,4-diaminodiphenylmethane.

3. The preparation technology of a high temperature resistant epoxy energy storage film based on liquid crystal ordered structure according to claim 1 is characterized in that: In S1, the liquid crystal biphenyl type epoxy monomer is a tetramethyl biphenyl type epoxy monomer.

4. The preparation technology of a high temperature resistant epoxy energy storage film based on liquid crystal ordered structure according to claim 1, characterized in that: In S1, the sum of the molar numbers of the bisphenol A type epoxy monomer and the liquid crystal biphenyl type epoxy monomer: the curing agent=3:

2.

5. The preparation technology of a high temperature resistant epoxy energy storage film based on liquid crystal ordered structure according to claim 1, characterized in that: In S1, the magnetic stirring and oil bath heating melting treatment are specifically as follows: A magnetic bar was added, and the mixture was heated and melted in an oil bath using a magnetic stirrer while being magnetically stirred.

6. The preparation technology of a high temperature resistant epoxy energy storage film based on liquid crystal ordered structure according to claim 5, characterized in that: The oil bath heating temperature is 105° C., the stirring rate is 150-250 r / min, and the stirring time is 10 min.

7. The preparation technology of a high temperature resistant epoxy energy storage film based on liquid crystal ordered structure according to claim 1, characterized in that: In S2, the degassing treatment is specifically: The mixed molten liquid is placed in a vacuum drying oven and heated under reflux until no bubbles are generated.

8. The preparation technology of a high temperature resistant epoxy energy storage film based on liquid crystal ordered structure according to claim 7, characterized in that: The degassing treatment temperature is 105-110° C., and the degassing time is 3-5 minutes.

9. The preparation technology of a high temperature resistant epoxy energy storage film based on liquid crystal ordered structure according to claim 1, characterized in that: In S2, the heat curing treatment using the hot pressing method is specifically as follows: First, the mold is preheated, and then a PET release film is placed under the mold. The degassed mixed molten liquid is poured into a copper foil mold with a thickness of 10μm. Then another PET release film is covered on top of the mold, placed in the middle of a mirror-smooth stainless steel plate, and put into a hot press for step-by-step heating and curing.

10. The preparation technology of a high temperature resistant epoxy energy storage film based on liquid crystal ordered structure according to claim 9, characterized in that: The temperature of the preheating treatment is 100-110° C., the temperature of the heating curing treatment is 105-200° C., and the curing time is 10 hours.

Citation Information

Patent Citations

  • Process for the polymerisation of alpha-olefins and method for preparing solid catalytic complexes for use in this polymerisation process

    EP0000007A1

  • Double liquid crystal structure toughened epoxy resin water-proof paint and preparation method thereof

    CN109913092A

  • Preparation method of liquid crystal epoxy for encapsulating high-voltage power device

    CN118006083A

  • Thermosetting liquid-crystal polyester composition and cured product thereof

    US20150247034A1